"Steeping" Of Health Expenditure Profiles - Florian Buchner; Jürgen Wasem (Universität Duisburg-Essen, Fachbereich Wirtschaftswissenschaften, 2004)
If health care expenditure for the elderly grows faster than for younger people, the expenditure profiles become "steeper" - we call that "steeping". Three instruments for measuring "steeping" are presented: (1) trend of the relation between per-capita-expenditure of the old and the young; (2) comparing the linear slopes of per-capita-expenditure in age groups; (3) trend in parameters of non-linear modelling of expenditure profiles. Using data of the largest German private health insurer over a period of 18 years, "steeping" could be observed by all three methods in most examined insurance plans. A prognosis for 2040 shows that per-capita-expenditure will increase by 128 %.
Keywords: 330; health care expenditure; expenditure profiles; demographics; Gesundheitskosten; Lebensalter; Prognose; Deutschland